Impact of weed control practices on weed suppression and crop performance in boro rice - Monira, Sirajam; Begum, Mahfuza; Uddin, Md Romij (Fundamental and Applied Agriculture, 2020)
Weed control is important to prevent yield loss and production costs, and to preserve quality grain. Therefore, a study was conducted during December 2016 to May 2017 to find out appropriate weed management practices in boro rice. Two boro rice varieties namely, BRRI dhan28 and BRRI dhan29 were included in the study. Twelve different combinations of herbicidal weed man- agements viz., No weeding, Amchlor 5G or Talon 52WP as pre-emergence, Supermix 18WP or Clean master 18WP as post-emergence, Amchlor 5G fol- lowed by Supermix 18WP or Clean master 18WP, Talon 52WP followed by Clean master 18WP or Supermix 18WP, Amchlor 5G + Supermix 18WP + Hand weeding at 35 DAT, Talon 52WP + Clean master 18WP + Hand weed- ing at 42 DAT, and Two hand weeding were included in this experiment following single factor randomized complete block design with three replica- tions. The maximum weed density (74.0 m−2 in BRRI dhan28 and 65.0 m−2 in BRRI dhan29) and biomass (38.2 g m−2 in BRRI dhan28 and 31.25 g m−2 in BRRI dhan29) were found in no weeding treatment and that of the lowest was obtained from Talon 52WP + Clean master 18WP + one hand weeding at 42 DAT. The highest grain yield (5.5 t ha−1 in BRRI dhan28 and 6.23 t ha−1 in BRRI dhan29), net return (58050 Tk ha−1 in BRRI dhan28 and 61229 Tk ha−1 in BRRI dhan29) and B:C ratio (1.81 in BRRI dhan28 and 1.86 in BRRI dhan29) were recorded when Talon 52WP + Clean master 18WP + one hand weeding at 42 DAT was applied. The lowest was obtained from the unweeded plots of both varieties. Based on this results Talon 52WP + Clean master 18WP + one hand weeding at 42 DAT was the best weed management practice in terms of efficacy and economics for both boro rice varieties.